Immunomodulatory and antioxidant effects of functional aquafeeds biofortified with whole Laminaria digitata in juvenile gilthead seabream (Sparus aurata) - Marmelo, Isa; Dias, Marta; Grade, Ana; Pousão-Ferreira, Pedro; Diniz, Mário Sousa; Marques, António; Maulvault, Ana Luísa (Frontiers in Marine Science, 2024)
The increasing demand for healthy aquatic products has contributed to the rapid growth of aquaculture. Despite the many progresses, over the years, in aquaculture production, animal welfare and reduction of the stress induced by captivity remain a challenge in this sector, and overcoming it is fundamental to improve animal growth performance and resilience to environmental threats (e.g., disease outbreaks and/or climate change impacts). To address this challenge, aquafeeds biofortified with natural ingredients with functional properties, such as macroalgae, have emerged as a promising strategy to enhance fish immunity. The present study aimed at evaluating the potential of Laminaria digitata to improve juvenile gilthead seabream (Sparus aurata) physiological status and resilience, through the modulation of immunomodulatory and antioxidant responses. To explore this hypothesis, four independent treatments were carried out in which fish were fed with different experimental aquafeeds: control feed and biofortified feeds with 1.5%, 3% and 6% of whole L. digitata (incorporated as a dried and powdered ingredient). Fish (n=9) were collected from each treatment upon 30 and 60 days of biofortification in order to assess animal growth and condition indexes, haematological parameters, innate humoral parameters (antiprotease (AP) activity, peroxidase (POD) activity and immunoglobulin M (IgM)) and oxidative stress biomarkers (lipid peroxidation (LPO), catalase (CAT) activity, glutathione S-transferase (GST) activity, superoxide dismutase (SOD) activity and total antioxidant capacity (T-AOC)). Significant differences (α = 0.05) between treatments in biomarker responses were tested through a nested-design ANOVA, followed by Tukey HSD multiple comparisons. Pearson correlations between the different endpoints were also explored. Results indicate that a dietary inclusion of 1.5% L. digitata is the most effective biofortification dose, significantly improving antioxidant responses of S. aurata, by increasing levels of CAT, GST and T-AOC, along with the reduction in LPO levels. Additionally, the inclusion of 1.5% L. digitata enhances immunity by increasing the levels of IgM and POD, while maintaining the growth performance and condition indices of the fish. These findings underscore the potential utilization of L. digitata as a functional feed ingredient in aquaculture with relevant immune and antioxidant attributes.